Analysis on Existence of Positive Solutions for a Class Second Order Semipositone Differential Equations. (14th August 2020) - Wang, Yunhai; Yang, Xu
Abstract : In this paper, we study the existence of positive solutions of the following second-order semipositone system (see equation 1). By applying a well-known fixed-point theorem, we prove that the problem admits at least one positive solution, if f is bounded below.